A Review of Contemporary Thought in Women Rights : With Reference to Amina Wadud and Others - Aiysha Madani (Islamabad Poorab Academy, 2005)
With particular reference to Pakistan
Include Bibliography
Keywords: Women in Islam -- Pakistan -- Feminism